Reference ranges for d-dimer levels in malaysian women in the three trimesters of pregnancy - Mohmad Sallih, Nornattasa; Subbiah, Indhira; Ali, Aishah; Jackson, Nicholas (Malaysian Society of Pathologists, 2019)
Introduction: Plasma D-dimer levels rise progressively during pregnancy, so one cannot apply normal reference ranges, or the usual cut-off value (500ng/mL), for the exclusion of venous thromboembolism (VTE), in pregnant women. This study was carried out in pregnant Malaysian women in order to build applicable reference ranges for D-dimer. Materials and Methods: A cross-sectional study was conducted to measure D-dimer in healthy pregnant women, and a non-pregnant control group, using the quantitative HaemosIL D-dimer HS500 assay. Reference ranges were derived using CLSI ‘Robust’ methods, and differences between group medians were tested using the Kruskal-Wallis and Mann-Whitney U tests. Results: Plasma D-dimer levels were measured in 92 pregnant women (distributed across the three trimesters)and 31 control women. The medians (and reference ranges) in ng/mL were: Control 265 (<799); first trimester 481 (<1070); second trimester 1073 (357–1748); 3rd trimester 1533 (771–2410). There were significant differences between the D-dimer levels of each group and each of the other groups (P<0.001). Conclusions: Reference ranges for D-dimer in pregnant Malaysian women have been establised by this study. Whether these ranges can be used to determine cut-off levels for the exclusion of VTE at different stages of pregnancy is doubtful, as the levels rise continuously through pregnancy, and some very high outlying values occur in apparently normal near-term pregnancy. © 2019, Malaysian Society of Pathologists. All rights reserved.